PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Shophan Sophian; Jerry Eka Putra (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
Tax is one of the largest sources of state revenue, but the revenue target has not been achieved so far. This is one of the indications due to Tax avoidance by companies. This study aims to determine the effect of profitability and leverage on tex avoidance. The research population is banking companies listed on the Indonesia Stock Exchange in 2018-2020. Sources of data used in this study is secondary data. The sample in this study is the banking sector listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. This type of research is quantitative research. Based on the hypothesis test shows that X1 profitability has a negative effect on tax avoidance with a value of Prob. of 0.000 <0.05, while X2 Leverage has no effect on tax avoidance which is shown by the value of Prob. of 0.282 > 0.05